Les enseignantes et enseignants sont-ils égaux face aux contraintes organisationnelles au sein des établissements du second degré ? - Dominique Cau-Bareille (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article presents results from an action research carried out in France in the secondary education field at the request of two trade unions. The research aimed to improve our understanding of gender relations in teaching and to shed light on harassment issues, which are mainly reported by women. The theme was approached from the angle of professional commitment by cross-referencing the ergonomic model of work activity, documented through a set of reflexive interviews, with the activity system model.It is shown that when women have children, most of them reduce their commitment to non-teaching, education-related tasks which are nonetheless essential to the effective functioning of secondary schools. This situation creates tension in establishments. The women need their efforts to care for their children to be accommodated by school administrators. The latter respond by putting pressure on women to take on additional tasks, presenting this as a mutually beneficial arrangement. It is likewise shown that these strategies for managing the interfaces between the different spheres of life have a negative impact on women’s working conditions and their careers.